PENGARUH PUPUK EKOENZIM TERHADAP HASIL RUMPUT GAJAH KATE (Pennisetum purpureum cv. Mott) PADA PEMOTONGAN KEDUA - Yusra,, F.A.,; Kusumawati,, N.N.C.; Roni, N.G.K. (Fakultas Peternakan Universitas Udayana, 2025)
Dwarf elephant grass (Pennisetum purpureum cv. Mott) is a tropical forage that is easyto develop, has high production, can be used as animal feed, and its productivity can beincreased to produce productivity through fertilization ecoenzyme. This study aims todetermine the results of dwarf elephant grass (Pennisetum purpureum cv. Mott) in the secondcutting fertilized with ecoenzyme fertilizer. The study was conducted at the Greenhouse of theSesetan Research Station, Faculty of Animal Husbandry, Udayana University, Jalan RayaSesetan Gang Markisa, Denpasar which lasted for October 2024 until January 2025 frompreparation to cutting. The experimental design used was a completely randomized design(CRD) consisting of five treatments and six replications, so there were 30 experimental pots.The treatments were as follows: D0: 0 l ha-1; D1: 5,000 l ha-1; D2: 10,000 l ha-1; D3: 15,000 l ha-1; D4: 20,000 l ha-1. The variables observed in the study were: leaf dry weight, stem dryweight, total dry weight of forage, root dry weight, ratio of leaf dry weight to stem dry weight,ratio of total dry weight of forage to root dry weight. The results showed that the application ofecoenzyme fertilizer with a dose of 15,000 l ha-1 produced the highest dry weight of leaves ,dry weight of stems and total dry weight of forage. It can be concluded that ecoenzymefertilizer increases the yield of kate elephant grass (Pennisetum purpureum cv. Mott) at thesecond cutting, and the ecoenzyme fertilizer dose of 15,000 l ha-1 gave the best results. ABSTRAK Rumput gajah kate (Pennisetum purpureum cv. Mott) adalah hijauan makanan ternaktropik yang mudah dikembangkan, produksinya tinggi, dapat dimanfaatkan sebagai makananternak ruminansia. Produktivitasnya dapat ditingkatkan melalui pemupukan ekoenzim.Penelitian ini bertujuan untuk mengetahui hasil rumput gajah kate (Pennisetum purpureum cv.Mott) pada pemotongan kedua yang dipupuk dengan pupuk ekoenzim. Penelitian dilaksanakandi Rumah Kaca Stasiun Penelitian Sesetan, Fakultas Peternakan, Universitas Udayana, JalanRaya Sesetan Gang Markisa, Denpasar yang berlangsung selama bulan Oktober 2024 hinggaJanuari 2025 mulai dari persiapan sampai pemotongan. Rancangan percobaan yang digunakanadalah rancangan acak lengkap (RAL) terdiri dari lima perlakuan dan enam kali ulangan,sehingga terdapat 30 pot percobaan. Perlakuan sebagai berikut: D0: 0 l ha-1; D1: 5.000 l ha-1;D2: 10.000 l ha-1; D3: 15.000 l ha-1; D4:20.000 l ha-1. Variabel yang diamati dalam penelitianyaitu: berat kering daun, berat kering batang, berat kering total hijauan, berat kering akar, nisbahberat kering daun dengan berat kering batang, nisbah berat kering total hijauan dengan beratkering akar. Hasil penelitian menunjukkan pemberian pupuk ekoenzim dengan dosis15.000 l ha-1 menghasilkan berat kering daun, berat kering batang dan berat kering total hijauanpaling tinggi. Dapat disimpulkan bahwa pupuk ekoenzim meningkatkan hasil rumput gajah kate(Pennisetum purpureum cv. Mott) pada pemotongan kedua, dan dosis pupuk ekoenzim 15.000 lha-1 memberikan hasil terbaik)